Tracking Global Adaptation: Indicators and LDC Priorities at COP29 - CGIAR Climate Change Impact Platform (CGIAR Climate Change Impact Platform, 2024)
As the global community converges on COP29, the focus has shifted from defining an overarching goal for climate adaptation to identifying indicators that can be applied globally to measure progress toward the agreed targets and support their effective implementation. The success of COP29’s adaptation agenda hinges on its ability to facilitate both the measurement of progress and the implementation of actionable strategies, reflecting a deep understanding of the diverse challenges different regions face. The outcomes will facilitate a decision on adaptation indicators under the GGA at COP30, making it imperative that efforts to measure and implement adaptation actions reflect the realities and needs of those on the frontlines of climate impacts.